Dual temperature- and pH-responsive polymeric micelle for selective and efficient two-step doxorubicin delivery. Issue 47 (6th June 2017) - Hiruta, Yuki; Kanda, Yuki; Katsuyama, Naoya; Kanazawa, Hideko
Abstract : Dual responsive polymeric micelle enabled selective intracellular uptake with thermal stimulation and effective release of doxorubicin at acidic endosomal pH. Abstract : We report a polymeric micelle drug delivery system, which enables selective intracellular uptake with external thermal stimulation, and effective release of a drug at internal acidic endosomal pH. We developed a dual temperature- and pH-responsive polymeric micelle composed of a temperature-responsive corona segment with poly( N -isopropylacrylamide- co -dimethylacrylamide) [P(NIPAAm- co -DMAAm)] and a pH-responsive core segment with poly[2-(diisopropylamino)ethyl methacrylate] (PDPA ). A dual temperature- and pH-responsive amphiphilic diblock copolymer was synthesized by reversible addition–fragmentation chain transfer (RAFT) polymerization. The dithiobenzoate end-group was removed with radical-induced ester exchange. This copolymer formed nano-sized micelles in aqueous solution, and encapsulated anti-cancer agent, doxorubicin (DOX). The resultant micelles exhibited a temperature-dependent phase transition at a temperature slightly higher than body temperature, and intracellular uptake of encapsulated DOX was accelerated above the phase transition temperature. A transition from neutral to positive charge, leading to micelle disassembly, accelerated the release of Nile red as a model drug. The cytotoxicity of doxorubicin (DOX)-loaded dual temperature- and pH-responsive micelles against human cervical cancer HeLa cells was significantly greater at 42 °C than at 37 °C, while no significant temperature-dependent cytotoxicity was observed with DOX-loaded micelles that were only temperature-responsive. This proof-of-concept synergistic two-step delivery system with enhanced intracellular uptake upon external thermal stimulation and rapid release of DOX at internal acidic endosomal pH was effective against tumor cells in vitro .